Factors related to burnout among secondary school teachers - Roslan, Samsilah; Md Nor, Sharifah; Mahyuddin, Rahil; Che Hassan, Norlizah (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
All the processes involved in education, from planning, delivery, managing classroom and evaluation are mainly carried out by teachers. Teaching, therefore, is a complex and demanding profession. The purpose of this study is to investigate the perception of secondary school teachers on changes in their burn out levels through years of teaching. In this regard, influencing factors such as work conditions and teachers' commitment were also studied to see the subsequent effect on teacher burnout. This study employed the survey research method, involving 304 teachers from 16 schools in the state of Selangor. Questionnaires were utilized to obtain data which were analyzed descriptively using means, percentages, correlation coefficients, and t-test. The findings show that there is a significant increase in teachers' level of burnout. Detailed observation show that there is an increase in mean score for every indicator of burnout. The correlation analysis shows that there is an increase in the strength of negative correlation between teachers’ level of burnout with teachers' commitment and working conditions.